2007
DOI: 10.1088/0953-8984/19/32/326213
|View full text |Cite
|
Sign up to set email alerts
|

High-field magnetization and magnetic structure of Tb3Co

Abstract: The measurements of the magnetization in high steady and pulsed fields together with neutron diffraction measurements on a powder sample and on a single crystal have been performed to study the magnetic state of the Tb 3 Co compound. It has been shown that the modulated antiferromagnetic structure which exists in Tb 3 Co below T N = 82 K transforms to the incommensurate magnetic structure with a strong ferromagnetic component along the c-axis with further cooling below the critical temperature T t ≈ 72 K. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 31 publications
9
33
0
Order By: Relevance
“…Meanwhile, the Curie temperatures of other rapidly quenched R 3 Co alloys (R ¼ Nd, Tb, Dy) [17] are observed to be close to the magnetic ordering temperatures for their polycrystalline counterparts [7,18,19]. As was mentioned above, the gain in the exchange energy in the amorphous Gd 3 Co alloy was suggested to result from the appearance of a magnetic moment on Co atoms.…”
Section: Resultssupporting
confidence: 56%
“…Meanwhile, the Curie temperatures of other rapidly quenched R 3 Co alloys (R ¼ Nd, Tb, Dy) [17] are observed to be close to the magnetic ordering temperatures for their polycrystalline counterparts [7,18,19]. As was mentioned above, the gain in the exchange energy in the amorphous Gd 3 Co alloy was suggested to result from the appearance of a magnetic moment on Co atoms.…”
Section: Resultssupporting
confidence: 56%
“…Among the rare-earth intermetallic compounds, R 3 T (T = Co, Ni) compounds possess the highest content of rare-earth metal within the binary R − T systems and exhibit a rich variety of physical properties: unconventional superconductivity [7,8], charge density wave [9], giant magnetoresistance effect [10,11], multi-component magnetic structures exhibiting coexistence of commensurate and incommensurate propagation vectors [12,13], field-induced magnetic phase transitions [13][14][15][16] and giant magnetocaloric effect [17][18][19][20]. R 3 T compounds crystallize in a low-symmetry orthorhombic structure of the Fe 3 C type described with the space group P nma [21].…”
Section: Introductionmentioning
confidence: 99%
“…The commensurate magnetic structures ͑although, different from Er 3 Co case͒ were also found in other R 3 Co compounds with Kramerstype ions, R = Dy and Nd. 3,11 This is in contrast to the incommensurate magnetic structure established for the systems with non-Kramers rare earth, e.g., Ho 3 Co and Tb 3 Co. 5,6 The type of the magnetic structure within R 3 Co series can be understood on the base of the periodic field model which takes into account the periodic exchange field and CEF effects. 12 According to this model an incommensurable magnetic structure may be observed down to low temperatures when a non-Kramers R 3+ ion has a nonmagnetic singlet ground state due to splitting of the multiplet by lowsymmetry CEF.…”
mentioning
confidence: 98%
“…However, more recent studies using new generation of neutron-scattering techniques have revealed that some of R 3 Co͑R =Ho, Tb͒ compounds exhibit much more complex magnetic structures. 5,6 The structures turn out to be incommensurate not only just below the magnetic ordering point but down to the lowest temperatures as well. We proposed recently that the non-Kramers character of the rare-earth ions is responsible for the incommensurability of the magnetic structures of these R 3 T compounds at low temperatures.…”
mentioning
confidence: 98%
See 1 more Smart Citation